Spinal dural arteriovenous fistula: a case-based review - Pore, Gargee M.; Gorthi , Brig S. P. (International Journal of Advances in Medicine, 2024)
Spinal dural arteriovenous fistula is an abnormal connection between radicular arteries and spinal venous plexus. This condition is relatively rare with annual incidence of five-ten cases per million. We present a case of a 62-year-old male with complaints of tingling in feet since six months and weakness in legs since 1 hour. Lower limb weakness progressed over a day to complete paralysis and bladder incontinence. Magnetic resonance imaging (MRI) spine showed a dural hypointensity over D6-D11 with abnormal vessels around spinal cord. Patient underwent spinal angiography which showed an intramedullary arteriovenous malformation causing compression. Arterial embolization was done within 24 hours from symptom onset and he ambulated within a week. AV malformations are a rare cause of compressive myelopathy presenting with acute paraplegia. Advances in endovascular techniques have made it possible to treat them early and prevent irreversible damage.